Engaging farmers in the selection and ranking of seeds varieties, in Bihar - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Bioversity International, supported by CCAFS, is working with farmers to test seed varieties to find out which perform the best in different climatic conditions. Farmers sow different seed varieties of wheat on their own fields and rank them according to performance. This is further evaluated and ranked by researchers to identify the varieties best suited to a particular local context. This video is filmed in Rajapaker, Bihar, in North Eastern India in 2013. Read a related blog story http://ow.ly/ufxCT